LANGUAGE VARIATIONS USED BY TRANSGENDER INDIVIDUALS AS LANGUAGE IDENTITY IN DENPASAR, BALI - Anwari, Anwari; Kurniawati, Eka; Isnina, Fathimah (Linguistik : Jurnal Bahasa dan Sastra, 2025)
This study aims to describe the kinds of language variations used by transgender individuals in Jl. Bungtomo Denpasar, Bali. This research applied field observation and was supported by interviews and recording techniques. The result shows that transgender language in Denpasar, Bali, can be categorized into singular subject, question word, demonstrative pronoun, noun, verb, adjective, and adverb. The phenomenon of language used by transgender individuals as their language variation to convey wishes in their social community. They also addressed it in code language to communicate with their social gender. On the other hand, they felt comfortable with their transvestite relationship in daily communication rather than standard language. They also considered that their variation of language is their own language that other people will not understand what is being said by them. This language was not born in the safe space of an intergovernmental association, but it was used in the dark area of transvestite prostitution. According to them, this jargon can only be used if it is used by speakers of the language. There are two conditions for encouraging the birth of this language. First, they sold themselves and were afraid of being harassed by their consumers. Second, before the pornography law existed, they realized that their sexuality was deviant.